2020
DOI: 10.1101/2020.10.15.340265
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Arachidonic acid metabolism controls macrophage alternative activation through regulating oxidative phosphorylation in PPARG dependent manner

Abstract: Macrophages polarization is mainly controlled by metabolic reprogramming in microenvironment, thus leading to distinct outcomes of various diseases. However, the role of lipid metabolism in the regulation of macrophage alternative activation is incompletely understood. Using human THP-1 and mouse bone marrow derived macrophages polarization models, we revealed a pivotal role for arachidonic acid metabolism in controlling the polarization of M1 and M2 macrophages. We demonstrated that M2 macrophage polarization… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…Experimental studies by Jiang et al found that M1 macrophages can be utilized to predict a patient's prognosis for ESCC by preventing ESCC cell migration and invasion [164]. By integrating transcriptomic and lipid metabolomic profiling, a large number of fatty acids and lipid mediators are pan-agonists of peroxisome proliferator-activated receptors (PPARs), and arachidonic acid, unsaturated fatty acid, significantly affects esophageal squamous cell carcinoma by regulating peroxisome proliferator-activated receptor gamma (PPARg) and OXPHOS M2 polarization in macrophages [165].…”
Section: Esophageal Cancer Lipid Metabolism On Tumor-associated Macro...mentioning
confidence: 99%
“…Experimental studies by Jiang et al found that M1 macrophages can be utilized to predict a patient's prognosis for ESCC by preventing ESCC cell migration and invasion [164]. By integrating transcriptomic and lipid metabolomic profiling, a large number of fatty acids and lipid mediators are pan-agonists of peroxisome proliferator-activated receptors (PPARs), and arachidonic acid, unsaturated fatty acid, significantly affects esophageal squamous cell carcinoma by regulating peroxisome proliferator-activated receptor gamma (PPARg) and OXPHOS M2 polarization in macrophages [165].…”
Section: Esophageal Cancer Lipid Metabolism On Tumor-associated Macro...mentioning
confidence: 99%